2019
DOI: 10.3389/fpubh.2019.00391
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mental Health Care in Developing Countries Through Digital Technologies: A Mini Narrative Review of the Chilean Case

Abstract: The uneven distribution of mental health resources contributes to the burden of mental disorders in vulnerable groups, especially in developing countries. Internet-based interventions and digital technologies can contribute to reducing the gap between high prevalence of mental disorders, demand for treatment, and access to mental health care, thereby reducing inequities in mental health. This mini review summarizes the current state of the field of e-mental health research in Chile, showing its progress, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
0
30
0
8
Order By: Relevance
“…Another review on RCTs on the effectiveness of occupational e-mental health concluded the need for more detailed and specific effectiveness research [ 246 ]. A narrative review on digital mental health in developing countries reported a shortage of studies on the effectiveness and cost-effectiveness of the investigated internet-based programs [ 166 ]. A review on the effectiveness of mobile apps reported a lack of clinically validated evidence on the efficiency of most available apps [ 191 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another review on RCTs on the effectiveness of occupational e-mental health concluded the need for more detailed and specific effectiveness research [ 246 ]. A narrative review on digital mental health in developing countries reported a shortage of studies on the effectiveness and cost-effectiveness of the investigated internet-based programs [ 166 ]. A review on the effectiveness of mobile apps reported a lack of clinically validated evidence on the efficiency of most available apps [ 191 ].…”
Section: Discussionmentioning
confidence: 99%
“…En el contexto de la salud mental, si se le compara con otras áreas de la neuropsiquiatría tanto a nivel mundial como en el medio local, como es el caso del Grupo de la Dra. Graciela Rojas en la Universidad de Chile [36][37][38][39][40] , la salud digital ha tenido un lento pero sostenido desarrollo en el ámbito de las Demencias. Así, los dispositivos móviles, tabletas, relojes inteligentes, trajes con sensores incluidos y aplicaciones (APP), constituyen un conjunto de herramientas tecnológicas que nos ofrecen una gran oportunidad para apoyar el diagnóstico precoz y monitoreo remoto de una población que envejece rápidamente 41,42 .…”
Section: Demencias Y Algunas Soluciones Digitalesunclassified
“…7 , 8 Nevertheless, these countries did not give much attention to major health issues. 9 , 10 This imposes a significant burden on the economy and well-being of the society in these countries. The productivity loss due to mental disorders, treatment costs to mentally ill people, and the exposure of these people to other co-morbidities forced governments to depend on foreign aids.…”
Section: Introductionmentioning
confidence: 99%